International survey of De-implementation of initiating parenteral nutrition early in Paediatric intensive care units - Esther van Puffelen; An Jacobs; Charlotte J. M. Verdoorn; Koen F. M. Joosten; Greet van den Berghe; Erwin Ista; Sascha C. A. T. Verbruggen (BMC, 2019)
Abstract Background Initiating parenteral nutrition (PN) within 24 h in critically ill children is inferior to withholding PN during the first week, as was found in the PEPaNIC study. The aims of this study were to investigate de-implementation of early initiation of PN at PICUs worldwide, and to identify factors influencing de-implementation. Methods A cross-sectional online survey was conducted (May - October 2017), consisting of 41 questions addressing current PN practices, the degree of de-implementation, and factors affecting de-implementation. Results We analysed 81 responses from 39 countries. Of these 81 respondents, 53 (65%) were aware of the findings of the PEPaNIC study, and 43 (53%) have read the article. In these 43 PICUs, PN was completely withheld during the first week in 10 PICUs, of which 5 already withheld PN (12%), and 5 de-implemented early initiation of PN (12%). Partial de-implementation was reported by 17 (40%) and no de-implementation by 16 (37%). Higher de-implementation rates were observed when the interpreted level of evidence and grade of recommendation of PEPaNIC was high. Predominant reasons for retaining early initiation of PN were concerns on withholding amino acids, the safety in undernourished children and neonates, and the long-term consequences. Furthermore, the respondents were waiting for updated guidelines. Conclusions One year after the publication of the PEPaNIC trial, only two-thirds of the respondents was aware of the study results. Within this group, early initiation of PN was de-implemented completely in 12% of the PICUs, while 40% asserted partial de-implementation. Increasing the awareness, addressing the intervention-specific questions and more frequently revising international guidelines might help to accelerate de-implementation of ineffective, unproven or harmful healthcare.